(untitled) (Al-Mansour Journal, 2022)
The change of the structure and environment of the system of Iraqi bank and great new management to conform and to convenient with those international bank requirements, therefore and that management helping the bank to achieve its objective and growth. The research focuses on the study of structure of the bank system according to international requirement formed by to development Risk Management, what its types and concept and the relation between the risk management and internal audit. The practical part has used questionnaire, which distributed on the two bank, first one belong the public sector AL-Rasheed Bank –main branch and the second belong the private sector United bank for Investment –main branch. The questionnaire consist of two part, first part regards with the procedures which followed by the internal audit in auditing and evaluating risk management and the second part specific with the role of the internal auditor to success the risk management. The comparative study has hold between the two banks, the result of the comparative study found there was no significant difference with part one, but there has significant with second part .United bank for Investment shall provide a sufficient number of auditors and employee with experiences in accounting, management and financial banking field ,the central bank as an observing side shall ensure that the bank committed to provide and implementation the basic requirement for management risks.